PENGELOLAAN DAN PENGEMBANGAN TEMPAT PENDARATAN IKAN AIR TAWAR KOTA BANJARMASIN - Sulaiman Sulaiman; Idiannor Mahyudin; Ahmadi Ahmadi (EnviroScienteae, 2022)
Fishery production from public waters has contributed greatly to the development of the fisheries and marine sector. This study aims to analyze and develop a place to find freshwater fish in the city of Banjarmasin. The research location was determined purposively (purposive sampling) was the Banjarmasin City Freshwater Fish Landing Site as one of the Regional Technical Service Units (UPTD) at the Banjarmasin City Food Security, Agriculture and Fisheries Service. Data analysis was done by analyzing the condition of the Banjarmasin Freshwater TPI and SWOT analysis (Strengths, Weaknesses, Opportunities, Threaths). The condition of fisheries at the Fish Landing Place (TPI) in Banjarmasin is still very high, this can be seen from the activities that take place every day, the number and value of fish production throughout 2021, the number of fishing boats moored, and fish transport cars whose resources continue to increase. , as well as the area of land that has not been used optimally. One of the strengths that support the existence of TPI is the location of TPI Air Tawar in Banjarmasin City which is very strategic with road access that is very easy to reach, both by land and water.